STUDI PENGGUNAAN KABEL T DAN SENAR NILON SEBAGAI MATA POTONG ALTERNATIF PADA MESIN PEMOTONG RUMPUT - Nofriady. H; Suryadi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2013)
Mower is one of many types of machines is used to cut the grass by the Farmers and Workers' City Park. By using this machine, the work will be lighter and faster. However, the eye piece of this machine is very harmful to user and other people around it if it is used to cut grass in rocky or gravel areas. By modyficating the eye piece of this machine by using the other materials is experfed the cutting process will be easier and not harm. In this study has been used the Nylon cable T string as alternatives eye piese. To testing the feasibility of T and cables Nylon Strings, testhing is conducted testing on grass cutting reeds. Tests using a standard eye pieces (2 eyes cut) can cut grass up area of 80 m 2 , whereas Nylon strings can only mow the lawn with an area of 24 m 2 , and T cable with an area 16 m 2 . Nylon strings T and the cable can be cut tall grass, but could not complete the test because of easily broken and easily tangled. From these results, it can be concluded that the alternative material (Nylon Strings and cables T) has not been feasible as an alternative cut eye on mowers